Determine Supporting Factors for the Successful Implementation of Electronic Medical Records in PHC Semarang City - Suhito, Hanif Pandu; Sholikun, Sholikun; Raniasmi, Prahita Indriana (Poltekkes Kemenkes Semarang, 2024)
The implementation of Electronic Medical Records (RME) in Semarang City health centers is a strategic step to increase the efficiency and effectiveness of health services. This research aims to identify factors that support the successful implementation of Electronic Medical Records (RME) in 39 Semarang City Health Centers. This research involved 110 respondents who were RME users, with various demographic characteristics such as age, gender, highest level of education, and years of work. Data was collected through an online survey using a Likert Scale-based questionnaire. Using the DeLone and McLean Model with the variables studied include system quality, information quality, service quality and user satisfaction. The results of multiple linear regression analysis show that system quality and information quality do not have a significant influence on user satisfaction, with t values of 1.515 (p=0.133) and -0.457 (p=0.649), respectively. However, service quality has a significant influence on user satisfaction, with a t value of 11.144 (p=0.000). This regression model explains that 86.7% of the variation in user satisfaction can be explained by the three independent variables, with an Adjusted R Square of 0.867. Based on this research, improving service quality is a key factor in increasing RME user satisfaction at the Semarang City Health Center. Effective implementation of RME can be encouraged by focusing on improving services to support the success of health digital transformation programs.